2014
DOI: 10.1186/s40100-014-0015-0
|View full text |Cite
|
Sign up to set email alerts
|

Consumer demand for alcoholic beverages in Switzerland: a two-stage quadratic almost ideal demand system for low, moderate, and heavy drinking households

Abstract: In this study, we estimate final demand for beverages with a particular focus on alcoholic beverages and calculate elasticities using microdata from the Swiss household expenditure survey from 2000 to 2009, which containsdata from more than 34,000 households. We estimate price and income responses for three household segmentslight, moderate, and heavy drinking householdsto assess whether higher alcohol consumption could be described by different price and income elasticities in comparison to lower alcohol cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Generally, according to the available evidence, it was concluded that systemwide estimations that include Deaton's model were set to conditional framework elasticity estimation. On the other hand, studies that deal with elasticity estimation in unconditional frameworks showed that those estimates are higher (mostly twice) in absolute values compared to conditional estimates [14,38,42,43,45,46].…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations
“…Generally, according to the available evidence, it was concluded that systemwide estimations that include Deaton's model were set to conditional framework elasticity estimation. On the other hand, studies that deal with elasticity estimation in unconditional frameworks showed that those estimates are higher (mostly twice) in absolute values compared to conditional estimates [14,38,42,43,45,46].…”
Section: Methodsmentioning
confidence: 97%
“…Analysis of all these factors is beyond the scope of this study. Moreover, most previous research in this area gave the estimates of conditional price and income elasticities [38,45,46,51,52]. Generally, according to the available evidence, it was concluded that systemwide estimations that include Deaton's model were set to conditional framework elasticity estimation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…P. Nelson, 2013J. P. Nelson, , 2015 and less price sensitive than light and moderate drinkers (Aepli, 2014;Manning, Blumberg, & Moulton, 1995;J. P. Nelson, 2013;Wagenaar et al, 2009).…”
Section: Relationships Tapered Offmentioning
confidence: 99%